Novel skeletal effects of glucagon-like peptide-1 (GLP-1) receptor agonists. Issue 1 (January 2018) - Mabilleau, Guillaume; Pereira, Marie; Chenu, Chantal
Abstract : Type 2 diabetes mellitus (T2DM) leads to bone fragility and predisposes to increased risk of fracture, poor bone healing and other skeletal complications. In addition, some anti-diabetic therapies for T2DM can have notable detrimental skeletal effects. Thus, an appropriate therapeutic strategy for T2DM should not only be effective in re-establishing good glycaemic control but also in minimising skeletal complications. There is increasing evidence that glucagon-like peptide-1 receptor agonists (GLP-1RAs), now greatly prescribed for the treatment of T2DM, have beneficial skeletal effects although the underlying mechanisms are not completely understood. This review provides an overview of the direct and indirect effects of GLP-1RAs on bone physiology, focusing on bone quality and novel mechanisms of action on the vasculature and hormonal regulation. The overall experimental studies indicate significant positive skeletal effects of GLP-1RAs on bone quality and strength although their mechanisms of actions may differ according to various GLP-1RAs and clinical studies supporting their bone protective effects are still lacking. The possibility that GLP-1RAs could improve blood supply to bone, which is essential for skeletal health, is of major interest and suggests that GLP-1 anti-diabetic therapy could benefit the rising number of elderly T2DM patients with osteoporosis and high fracture risk.